Bentuk dan Makna Sapaan al-Munādā terhadap Iyasu dalam Novel al-Ẓill al-Aswad Karya Najib Kailani - Malikussaleh, Malikussaleh; Mardiansyah, Yadi; Komarudin, Edi (Aphorisme: Journal of Arabic Language, Literature, and Education, 2026)
This study aimed to classify the forms of al-munādā used to address the main character, Iyasu, in Najib Kailani's novel Aẓ-Ẓill Al-Aswad, based on the speaker's social relationships, and to analyze the meaning of these forms within the relationships that underlie them. A descriptive qualitative approach was employed using the listen-and-record technique for 34 instances of al-munādā in which Iyasu served as the addressee. The data were drawn from 10 groups of speakers, categorized into three relational groups: Family, Court, and Public. The analysis combined Al-Ghalayyini's classification of al-munādā with Hymes' SPEAKING framework to uncover the context and purpose of the utterances. The results revealed seven variations of al-munādā forms, distributed differently across each relational category. The mufrad 'alam form was found only in the Family category, while the mudhāf form appeared in both the Family and Court categories, with lexical choices producing different meanings. The Family category dominated the use of forms of address, followed by the Court and the Public. In terms of meaning, forms of address in the Family category served to express emotional closeness; those in the Court category represented hierarchical relationships; while some forms used by Tafari were employed manipulatively to create dramatic irony in the narrative. These findings indicated a correspondence between the grammatical forms of al-munādā and the meanings they conveyed. The choice of al-munādā form not only reflected the rules of nahw but also served as a tool for marking social relations, power distribution, and communication strategies among characters.